GitHub codespaces course. (Pragmatic AI Solutions, 2022)
GitHub Codespaces Course A full introduction to Codespaces with practical examples This course will show you everything you need to know to be productive using GitHub Codespaces , a service that allows you to run a configurable development environment with one-click launch with a remote compute in the cloud. Being able to run Visual Studio Code in the cloud for any project with a pre-configured environment is going to allow you to concentrate on the learning if you are student, the teaching if you are a professor, or being plain productive if you are already a technologist. Learning Objectives This course goes through some of the basics of using default Codespaces environments, but it also goes into configuring environments to take advantage of its best features, including: Learning about Codespaces uses and how it fits for learning, teaching, or working in projects Running default Codespaces and configuring it in your GitHub account Configuring Codespaces for different development environments Applying practical examples in Codespaces environments using Docker, Python, and many other tools About your instructor Alfredo Deza has over a decade of experience as a Software Engineer doing DevOps, automation, and scalable system architecture. Before getting into technology he participated in the 2004 Olympic Games and was the first-ever World Champion in High Jump representing Peru. He currently works in Developer Relations at Microsoft and is an Adjunct Professor at Duke University. This solid background in technology and teaching, including his experience creating courses with Codespaces is seen throughout this course, where you will get a first-hand experience with practical examples as well as applicable configuration for any development environment. Resources Python Bootcamp Pytest Master Class Practical MLOps book What is GitHub Codespaces Azure Codespaces Template.